Molecular Analysis and Detection of Antibiotic Resistance Genes in Aerobic Bacteria Isolated from Bacteremia Patients at Tertiary Healthcare Institutions - O, George W.; V, Anyiam I. (African Journal of Clinical Medicine and Pharmacy Research, 2025)
Bacteremia is the presence of bacteria in the bloodstream. Aerobic bacteria, such as Escherichia coli, Klebsiella pneumoniae, and Staphylococcus aureus, are common causes of bacteremia and have developed resistance to various antibiotics. The study aims to analyze and detect antibiotic resistance genes of aerobic bacteria isolated from bacteremia patients in tertiary healthcare institutions. A total of 110 blood specimens were collected from patients attending Federal Medical Centre Yenagoa and Gloryland INRI Medical Centre Yenagoa. The specimens were analyzed by culture, biochemical test, and molecular methods. Out of the 110 blood cultures, 4.5% were positive. Organisms isolated were Staphylococcus aureus (60%) and Klebsiella pneumoniae (40%). The isolates were more common in males (80%) than females (20%). The prevalence of bacteremia between children and adults was 5% and 4.4% respectively. Antibiotic susceptibility test the gram positive isolates showed maximum resistance to ampiclox (100%), zinnacef (100%), erythromycin (100%), and 66.7% resistance to amoxacillin and rocephin respectively. However, high susceptibility was shown to gentamicin (100%), levofloxacin (100%), and ciprofloxacin (66.7%). The gram negative isolates showed maximum resistance to ciprofloxacin (100%) and 50% resistance to cefotaxime, gentamicin, chloramphenicol, ceftriaxone, levofloxacin ampicillin/sulbactam and co-trimoxazole respectively. Nevertheless, maximum susceptibility was shown to ofloxacin, tetracycline, and azithromycin with 100% respectively. The molecular detection of antibiotics resistance genes revealed the presence of CTX-M (100%), and QnRA (33.3%) in the S. aureus strains. CTX-M (100%), QnRA (100%), and QnRB (50%) were seen in the K. pneumoniae strains. However, the aaC gene was found neither in the S. aureus strains nor K. pneumoniae strains. Phylogenetic analysis using 16s rRNA sequences identified bacterial isolates; S. aureus and K. pneumoniae. These results underscore the complexity of resistance patterns and the molecular mechanisms driving them in the studied pathogens. Crucial effort should be put in place to enhance surveillance and regularly update resistance profiles to guide treatment.